Population Growth and its Spatial Dimension and its Impact on the Sustainable Standard of Residential land Uses. Najaf District Case Study for the Period 2020-2025 (Journal of University of Babylon for Engineering Sciences, 2021)
There is an impact of population growth on urban land uses, and it is necessary to prepare and predict the possible or potential results, and the problems it causes as a result of poor planning, management and implementation, not to mention the negligence in calculating the direction and size of the relationship between population growth and urban growth, in particular urban saturation and diversity. The potential effect of population growth, and in order not to wait for the problem to occur, we must take the initiative and recognize that there is a local and regional problem in the issue of housing and population growth, meaning that the housing stock does not meet the housing need due to the increasing population growth, which creates an increasing gap between them. The research adopted a descriptive analytical approach to real historical data for both residents and residential areas and the sustainable standard share of residential use for Najaf district. Which was divided into six zones to make it easier for us to study them, analyze their variables, and predict the growing sustainable standard of residential areas for the next five years in the study area. One of the most important results is that there is a mismanagement and wrong estimation of population growth that has generated urban saturation in urban land uses. Foremost among them is the varying impact of population growth on the sustainable housing standard, which, of course, has created a decent and acceptable sustainable standard ratio for residential use and another that is unsustainable, inappropriate and unacceptable for residential use, both of them are located between the upper and lower limits of the standard and sometimes out of  standards. In order to maintain the sustainability of the growing standard to conform the reality of urban land uses, it is necessary to move or relocate the developing population within or outside zone to create sustainable harmony between population and housing under a growing and sustainable standard.